Characteristics linked to mortality risk among individuals with drug use disorders enrolled in drug rehabilitation facilities in Japan - Satomi Mizuno; Takuya Shimane; Satoshi Inoura; Maki Kitamura; Toshihiko Matsumoto (PCN Reports)
Abstract Aim This study evaluated survival rates and examined characteristics associated with mortality among individuals with drug use disorder (DUD) enrolled in drug addiction rehabilitation facilities in Japan. Methods This longitudinal cohort study, conducted from October 2016 to October 2021, followed 361 individuals with DUD residing in drug addiction rehabilitation centers nationwide. Participants had a mean age of 41.1 years (standard deviation 9.7) and most were men. About half had not completed high school or had criminal records, including drug offenses. Data were collected through eight follow‐up assessments conducted approximately every 6 months. Kaplan–Meier analysis was used to calculate 5‐year survival rates, and age‐specific mortality was evaluated among participants. A Cox proportional hazards model identified characteristics influencing mortality risk, including demographic factors, medical history, and abstinence maintenance. Hazard ratios and 95% confidence intervals were calculated to assess mortality risk. Results The survival rate was 95.4%, with 14 deaths recorded. Mortality was highest among participants aged over 60 years. Age and the presence of bloodborne or sexually transmitted infections were significantly associated with higher mortality, while abstinence was associated with reduced mortality. Conclusion This study is the first to examine survival rates and mortality factors among individuals with DUD in drug addiction recovery centers in Japan. Findings suggest that these facilities may help prevent drug relapses and reduce mortality risk, while highlighting aging and infections as key factors linked to mortality.